Utilising a Suite of Isotopic and Elemental Tracers to Constrain Cryoturbation Rates and Patterns in a Non‐sorted Circle. (27th March 2017) - Jelinski, Nicolas A.; Yoo, Kyungsoo; Klaminder, Jonatan
Abstract: The empirical quantification of rates of material movement in cryoturbated soils has lagged behind the physical and chemical characterisation of these materials. We applied a novel suite of elemental (C, Hg), stable isotope ( 13 C) and radioisotope ( 137 Cs, 210 Pb, 14 C, 10 Be) tracers in conjunction with analytical and numerical models to constrain the rates and patterns of soil movement due to cryoturbation in a non‐sorted circle (NSC) near Abisko, Sweden. We present the first observations of the variability of 10 Be across a patterned‐ground feature, which facilitate the interpretation of subsurface peaks in soil organic carbon, Hg and 13 C and provide constraints on the surficial histories of cryoturbated materials. Apparent rates of surficial lateral movement across the NSC estimated from 137 Cs and 210 Pb (0–2.55 cm year −1 ) decreased with distance from its centre and were an order of magnitude greater than rates of subduction and subsurface movement estimated from 14 C (0.04–0.27 cm year −1 ). Novel estimates of the original surficial residence times of cryoturbated parcels based on excess 10 Be and Hg inventories ranged from 238 to 3940 years. Our results demonstrate the utility of the spatially explicit application of elemental and radioisotopic tracer suites to constrain cryoturbation rates in Arctic patterned ground. Copyright © 2017 John Wiley & Sons, Ltd.